Identification and comparison of factors behind mental turbulence of public and private university students - Tahsin, Md. Akil; Hannan, Sumaiya; Shifa, Fabiha Rumman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.